Higher education in management and its legitimacy (Journal of Management and Business Education, 2020)
Organizational legitimacy is an important consideration for the growth of private and public higher education. Unlike most state-sponsored institutions, the social acceptance of the private sector model is based on its ability to justify its own right to exist. But if private organizations must demonstrate their right to exist, institutional pressure forces public institutions to also demonstrate their legitimacy. Many of the considerations listed below are universities challenges and calls for action. Each of them represents issues that will partially contribute to their legitimacy. Now, business schools would be responsible for leading the implementation and development of university legitimacy, only to compensate their indifference on other occasions, such as, for example, when the movement for quality and excellence in university management began.
Keywords: higher education; business education; management; legitimacy